What nonnarcotic oral analgesics are the safe for patients taking warfarin?. Issue 12 (December 2017) - ElDabh, Andrew; Roett, Michelle A.
Abstract : EVIDENCE‐BASED ANSWER : The answer is not entirely clear. COX‐2 inhibitors appear safer than nonselective nonsteroidal anti‐inflammatory drugs (NSAIDs) for patients taking warfarin (SOR: B, cohort and case‐control studies). Acetaminophen increases the international normalized ratio (INR) in patients taking warfarin by 0.67 to 0.83 over placebo, but with unclear clinical effect (SOR: C, small RCTs with disease‐oriented outcomes).